Ethnic identity and educational outcomes of German immigrants and their children - Anna-Elisabeth Thum (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Identity can be an important driving force for educational performance. Immigrants and their children face the challenge of identifying with their host country's culture. This paper examines whether young immigrants and their children who identify stronger with the German culture are more likely to increase their educational outcomes. I use a concept of ethnic identity which is designed to capture Germanness in immigrants' day-to-day routine - based on self-identification, language skills and cultural habits. The research design takes into account the issue of endogeneity of ethnic identity in an educational outcome equation by measuring education and identity at different moments and by using an endogenous latent factor methodology. The paper finds that identification with the German culture has an overall positive effect on educational outcomes and diminishes and renders the educational gap between immigrants and the second generation insignificant. The papers results indicate that the second generation identifies stronger with the German culture than immigrants, no matter whether of German, European, Central European or Turkish background. Apart from the immigrant generation, own low educational attainment and high mother's educational attainment matter for identification with the German culture.
Keywords: 330